2017
DOI: 10.4236/jcdsa.2017.72013
|View full text |Cite
|
Sign up to set email alerts
|

Topical 40% <i>Loranthus europaeus</i> Ointment as an Alternative Medicine in the Treatment of Acute Cutaneous Leishmaniasis versus Topical 25% Podophyllin Solution

Abstract: Background: Cutaneous leishmaniasis (CL) is an endemic disease in Iraq, now is running in an outbreaks. Many therapies have been tried in treatment of the disease. Objective: Loranthus europaeus (LE) is a well-known medical plant and has many pharmacological effects in many in vitro studies. The aim of the study is to evaluate the effectiveness of 40% LE ointment and compared it with topical 25% podophyllin solution in treatment of acute CL. Patients and Methods: Thirty five patients with acute CL were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Antimicrobial activity could be attributed to the active substances of boiled extract of Loranthus europaeus such as tannins, terpenoids, flavonoids and alkaloids phyto-constituents, which are considered as antibacterial compounds. However, Uzochukwu Osadebe [33]., and EL-Sharquie [34], reported that the alcoholic extract contains polysaccharides and aldehydes, which accelerate wound healing and have antimicrobial activity, preventing secondary bacterial infections. The study of Al-Rubaee [35].…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial activity could be attributed to the active substances of boiled extract of Loranthus europaeus such as tannins, terpenoids, flavonoids and alkaloids phyto-constituents, which are considered as antibacterial compounds. However, Uzochukwu Osadebe [33]., and EL-Sharquie [34], reported that the alcoholic extract contains polysaccharides and aldehydes, which accelerate wound healing and have antimicrobial activity, preventing secondary bacterial infections. The study of Al-Rubaee [35].…”
Section: Resultsmentioning
confidence: 99%
“…The hemiparasite Loranthus europaeus (Loranthaceae), also known as mistletoe, is a plant native to Southeast Europe, Anatolia, Southern Russia, Iran and Iraq (Sharquie et al, 2017;Benabderrahim et al, 2019). Mistletoe, which is semi-parasitic, produces its own carbohydrates by photosynthesis while living in various host trees, but obtains the mineral and water needs necessary for nutrition from its hosts.…”
Section: Introductionmentioning
confidence: 99%